Experimental studies on the viscosity of TiO2 and Al2O3 nanoparticles suspended in a mixture of ethylene glycol and water for high temperature applications - Yiamsawas, Thaklaew; Mahian, Omid; Dalkilic, Ahmet Selim; Kaewnai, Suthep; Wongwises, Somchai (ELSEVIER SCI LTD, 2013)
Experimental investigations are performed to determine the viscosity of TiO2 and Al2O3 nanoparticles suspended in a mixture of ethylene glycol/water (EG-water, 20/80 wt%). The experiments are conducted at various volume fractions between 0% and 4% and a temperature range of 15-60 degrees C. Some comparisons are made between the experimental results and the theoretical models and correlations presented for viscosity in the literature. The results indicate that the theoretical models are not suitable to predict the viscosity of nanofluids. Finally, using the experimental data, a useful correlation is presented to predict the viscosity. To estimate the required pumping power in an energy device, in the first, the viscosity should be determined. Therefore, the results of the present work may be helpful in the design of energy devices. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Viscosity; Nanofluids; Experimental study; Theoretical models; High temperature; THERMAL-CONDUCTIVITY; HEAT-TRANSFER; TIO2-WATER NANOFLUIDS; OXIDE NANOPARTICLES; SUSPENSION; PARTICLES; Energy & Fuels; Engineering